PENGARUH LINGKUNGAN KERJA, KOMUNIKASI, DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN DI HOTEL RAFFLES JAKARTA - Febiola Putri Dasmayanti; Hariadi Hadisuwarno (Human Capital Development, 2019)
Purpose- The purpose of this study is to examine the effect of work environment, communication, and work discipline on employee productivity at Hotel Raffles Jakarta. Design/methology/approach The samples used in this study were 100 employees by purposive sampling method. Methods of data collection using questionnaires. Analysis of the data used is multiple linear regression. Findings- The results showed either simultaneously or partially, consist of work environment (X1), communication (X2), work discipline (X3) have a significant influence on employee productivity (Y). Researchers concluded that the better work environment, good communication, and the higher level of employee’a discipline will increase employee productivity. Variable work environment is the most dominant variables affecting employee productivity at Hotel Raffles Jakarta.